Functional and Structural Correlates of Memory in Patients with Mesial Temporal Lobe Epilepsy - Barnett, Alexander J.; Park, Min Tae M.; Pipitone, Jon; Chakravarty, M. Mallar; McAndrews, Mary Pat (Frontiers in Neurology, 2015)
Individuals with medial temporal lobe epilepsy (mTLE) often show material-specific memory impairment (verbal for left, visuospatial for right hemisphere) which can be exacerbated following surgery aimed at the epileptogenic regions of medial and anterolateral temporal cortex. There is a growing body of evidence suggesting that characterization of structural and functional integrity of these regions using MRI can aid in prediction of post-surgical risk of further memory decline. We investigated the nature of the relationship between structural and functional indices of hippocampal integrity with preoperative memory performance in a group of 26 patients with unilateral mTLE. Structural integrity was assessed using hippocampal volumes, while functional integrity was assessed using hippocampal activation during the encoding of novel scenes. We quantified structural and functional integrity in terms of asymmetry, calculated as (L - R) / (L + R). Factor scores for verbal and visual memory were calculated from a clinical database and an asymmetry score (verbal – visual) was used to characterize memory performance. We found, as expected, a significant difference between left and right mTLE groups for hippocampal volume asymmetry, with each group showing an asymmetry favoring the unaffected temporal lobe. Encoding activation asymmetry showed a similar pattern, with left mTLE patients showing activation preferential to the right hemisphere and right mTLE patients showing the reverse. Finally, we demonstrated that functional integrity mediated the relationship between structural integrity and memory performance for memory asymmetry, suggesting that even if structural changes are evident, ultimately it is the functional integrity of the tissue that most closely explains behavioral performance. Our findings argue for the incorporation of functional imaging data in clinical protocols aimed at determining the functional integrity of the MTL in surgical planning.